Comorbidity patterns and associated characteristics in children with obstructive sleep apnoea–hypopnoea syndrome in Shanghai, China: a cross-sectional study - Xiang Gao; Chen Chen; Yan Yang; Liang Zhou; Jianwei Shi; Dehua Yu; Hua Jin; Zhaoxin Wang; Jiaoling Huang; Ning Chen; Ziyun Li; Huining Zhou; et al. (BMJ Open)
Objectives Paediatric obstructive sleep apnoea–hypopnoea syndrome (OSAHS), which usually cooccurs with various diseases, significantly impacts health and social resources. Domestic paediatric OSAHS studies have not included comorbidity patterns or distribution characteristics. Thus, we investigated the comorbid characteristics of paediatric OSAHS in Shanghai, China.Design Large hospital-based cross-sectional study.Setting Paediatric ward medical data from the Pudong New Area, Shanghai, China from 2013 to 2016.Participants 4045 Chinese children aged 0–18 years.Primary and secondary outcome measures Paediatric OSAHS was diagnosed using the Paediatric Sleep Questionnaire with a cut-off score of 8 points. The outcomes were comorbidity patterns and their characteristics. χ2 tests were performed to compare differences among the top comorbidity patterns.Results Major comorbidities were otolaryngological morbidities. Among one-comorbidity patterns, OSAHS+chronic rhinitis (37.53%) and OSAHS+allergic rhinitis (28.13%) were most common. Among two-comorbidity patterns, OSAHS+chronic rhinitis +chronic exudative otitis media (10.88%), OSAHS+allergic rhinitis +chronic exudative otitis media (7.94%), OSAHS+allergic rhinitis +chronic tonsillitis (4.43%) and OSAHS+chronic rhinitis +chronic tonsillitis (4.23%) were most common. Males predominated in all comorbidity groups. Age differences for the top five patterns in both the one-comorbidity (p=0.035) and two comorbidities (p<0.001) groups were statistically significant. In the one-comorbidity group, patients were more likely to have one operation (p<0.001), and in the two comorbidities group, patterns of ‘OSAHS+chronic rhinitis +chronic exudative otitis media’ and ‘OSAHS+allergic rhinitis +chronic exudative otitis media’ were more common in the ≥2 operations group (p<0.001). Notably, the top five patterns of the 2-comorbidities group were significantly associated with the length of stay (LOS) (p<0.001), while those in the one-comorbidity group were not.Conclusion OSAHS+rhinitis (chronic rhinitis or allergic rhinitis) was the most common diagnosis. Age, number of operations, and LOS are significantly associated with the patterns. This emphasises the importance of better understanding complex otolaryngological comorbidity diagnoses and treatments in paediatric OSAHS to reverse clinical outcomes and save health resources.